INNOVATIVE METHODOLOGIES IN EARLY EFL EDUCATION: ENHANCING ENGLISH LANGUAGE ACQUISITION AMONG YOUNG LEARNERS - Mohinabonu Tagaeva (Web of Journals Publishing, 2025)
This study explores effective methods for teaching English to young learners (TEYL), focusing on communicative approaches, interactive activities, and age-appropriate strategies. Based on classroom observation and teacher interviews, the study identifies techniques that improve motivation, vocabulary retention, and speaking fluency in children aged 5–10. The findings highlight the importance of games, songs, and visuals in creating a child-friendly learning environment. The research draws upon qualitative data collected through classroom observations and semi-structured interviews with EFL educators across several primary institutions. Key findings indicate that the use of play-based learning, Total Physical Response (TPR), story-based instruction, and digital learning tools significantly contribute to vocabulary development, listening comprehension, and communicative confidence among young learners. The integration of visual, auditory, and kinesthetic elements was found to stimulate greater retention and meaningful language use, while fostering positive attitudes toward language learning.
Keywords: Communicative approaches, interactive activities, story-based instruction, digital learning tools, songs, visuals, auditory, play-based learning.